Evaluation of a quick one‐step sample preparation method for the determination of the isotopic fingerprint of rapeseed (Brassica napus): Investigation of the influence of the use of 2, 2‐dimethoxypropane on compound‐specific stable carbon and hydrogen isotope analyses by gas chromatography combustion/pyrolysis isotope ratio mass spectrometry. (10th March 2021) - Xia, Lili; Sakaguchi‐Söder, Kaori; Stanojkovski, Daniel; Schebek, Liselotte
Abstract : Rationale: Gas chromatographic analyses for vegetable oils require transesterification, which generally involves multiple steps, mainly to generate fatty acid methyl esters (FAMEs). A quick method based on acid‐catalyzed transesterification using 2, 2‐dimethoxypropane (DMP) enables the conversion in one step, in a single reactor. For compound‐specific stable carbon and hydrogen isotope analyses (C‐ and H‐CSIA) of individual fatty acids (FAs) in oil, the verification of this one‐step method has not yet been reported. Methods: In this study, we evaluated the feasibility of the one‐step method for C‐ and H‐CSIA of individual FAMEs in rapeseed samples. The focus was on the investigation of the influence of methanol, which was produced from the reactions of DMP with glycerol and water during transesterification, on the accuracy of isotope composition of FAMEs, consequently of the FAs. The reproducibility of the one‐step method was assessed by the measurement of the FAMEs from rapeseed and rapeseed oil. For the C‐ and H‐CSIA of individual FAMEs, a gas chromatography combustion/pyrolysis isotope ratio mass spectrometry system was used. Results: Our results showed that no significant differences arise in the carbon and hydrogen isotope compositions of the selected main FAMEs produced with and without DMP except for the H‐CSIA value of C18:3. The reproducibility of the one‐step method for rapeseed was in the range of ±0.1 mUr to ± 0.3 mUr for C‐CSIA and ±1 mUr to ±3 mUr for H‐CSIA of the main FAMEs. Conclusions: DMP improves the transesterification efficiency without influencing the accuracy of the C‐ and H‐CSIA of FAMEs. The performance of the one‐step method for rapeseed samples for the determination of C‐ and H‐CSIA values of FAMEs is satisfactory. Thus, the applicability of the one‐step method for isotopic fingerprint analyses of FAs in oilseeds is reported for the first time.